Implementasi Metode COPRAS dengan Pembobotan Entropy dalam Sistem Seleksi Koordinator Sensus Kecamatan (Koseka) - Ramadhan, Muhammad Antasari; Fakhriza, Muhammad (Program Studi Teknik Informatika Universitas Pamulang, 2024)
This research aims to optimize decision making in selecting KOSEKA (District Census Coordinator) candidates within the scope of the Langkat Regency Central Statistics Agency. The problem found in the KOSEKA selection process was that the selection process still used manual methods so that it was very time inefficient and had an impact on the final selection results not being in accordance with the required qualifications. For this reason, there must be a selection system which, if implemented, will produce effective and efficient decisions, namely utilizing a decision support system using the Entropy method as weighting criteria and Complex Proportional Assessment (COPRAS) as the final calculation method for each alternative. Based on the results of research conducted taking into consideration the criteria used, namely experience, training transport costs, communication skills, honesty, appearance and location of residence, a Utility value for each alternative has been obtained with the highest score, namely Claudia Riswandi (A8) who has a score 100%, followed by Aprida Br Sitepu (A2) in second place with a score of 97.69566969% and so on.